Sacred space and Anglo-Turkish relations: the politics of British churches, cemeteries and war graves in Turkey, 1825 to 1976 - Fisher, John (I. B. Tauris, 2024)
"Illuminating the interplay of religion and British diplomacy in Turkey within a broad time frame, This book explores the religious life of British expatriates in Turkey, and the politics of Anglican and other Christian spaces, from churches to war cemeteries and memorials, as they affected British relations with the Ottoman Empire and then Republican Turkey"--